Pemerolehan Bahasa Anak dalam Perspektif Psikolinguistik : Studi MLU, Kategori Kata, dan Pola Kalimat - Erfriani Sekar Talenta Simangunsong; Nur Fatimah; Huraiyah Jiratullah; Frinawati Lestarina Barus (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study discusses children's language acquisition from a psycholinguistic perspective with a focus on Meanlength of Utterance (MLU), word categories, and sentence patterns. Using a qualitative descriptive approach and case study, data were collected through participant observation, audio recording, speech transcription, and social context recording. The research sample consisted of three children aged 39, 47, and 50 months with Indonesian as their first language. The results showed that MLU values ​​increased with age, in accordance with Brown's theory, although there was individual variation. Analysis of word types showed that older children had a more diverse vocabulary, including nouns, verbs, adjectives, pronouns, and numerals. In addition, the sentence patterns used by children developed from simple structures such as SP to more complex structures such as SPOK. This study confirms that MLU can be an indicator of children's syntactic development and helps in language identification delays. The results of this study are expected to contribute to psycholinguistic studies and become a reference in the field of child language education and intervention